Palm Oil Plantations in West and Central Kalimantan, Indonesia: Sustainability Analysis Using a Hierarchy Process Method - Selfia Bintariningtyas; Evi Gravitiani; Dwi Prasetyani; Ika Alicia Sasanti; Aulia Hapsari Juwita (مجلة ديالى للعلوم الزراعية)
There are quite significant differences in the management of palm oil businesses in West Kalimantan and Central Kalimantan Provinces. In fact, West Kalimantan has a very large area of oil palm land, but its production output is smaller compared to Central Kalimantan province. Based on these facts, this research aims to determine the policy strategy for sustainable palm oil management, which includes economic, social, environmental and legal aspects to be implemented in the provinces of West Kalimantan and Central Kalimantan. This research applies the Analysis Hierarchy Process (AHP) method with a pairwise comparison matrix approach to calculate the weight of each index and create sustainable palm oil based on primary data collection through questionnaires. The research results show that in developing sustainable oil palm plantations, environmental aspects can be considered first, with a primary focus on oil palm land conservation. Conservation of oil palm land is an important part because it is a form of protection, restoration, improvement and maintenance of land functions in accordance with land capabilities and use. The results obtained from calculations carried out using the AHP model show that there are 3 policy alternatives, namely Agribusiness Public Partnership, Agribusiness Private Partnership, and Agribusiness Public - Private Partnership. This can provide benefits for economic growth through increasing agricultural productivity. Agribusiness Public-Private Partnerships have a very important role as a benchmark for sustainable palm oil plantation policies in Central and West Kalimantan.